In Vitro Characterization of Poly(Ethylene Glycol) Dimethacrylate-Nanofibrillated Cellulose as an Injectable Biomaterial for Herniated Nucleus Pulposus Substitute - Widiyanti, Prihartini; Firda, Yurituna; , Aminatun; Wibowo, Herry (Folia Medica Indonesiana, 2024)
Highlights: 1. Novel synthetic biopolymer hydrogels were successfully prepared from pristine poly(ethylene glycol) dimethacrylate (PEGDMA) and nanofibrillated cellulose (NFC) using the photopolymerization method. 2. PEGDMA-NFC biocomposite hydrogel can be developed as an affordable biomaterial for herniated nucleus pulposus substitute, with the potential to meet clinical application standards. Abstract Herniated nucleus pulposus develops when the intervertebral disc portudes through the annulus fibrosus due to the rupture of the annulus fibrosus or a decrease in proteoglycans. Hydrogel implant material can be injected into the disc space to restore disc thickness caused by disc degeneration with minimal invasiveness. This study aimed to characterize poly(ethylene glycol) dimethacrylate-nanofibrillated cellulose (PEGDMA-NFC) in vitro as a potential biomaterial for herniated nucleus pulposus substitute. This study utilized PEGDMA-NFC to treat first-degree herniated nucleus pulposus using the photopolymerization method. PEGDMA was selected because of its hydrophilic ability to produce hydrogel. The addition of NFC to the PEGDMA precursor was expected to show mechanical properties as a hydrogel bio composite candidate. The characterization of PEGDMA-NFC was conducted using three tests: Fourier-transform infrared spectroscopy (FTIR), viscosity assessment, and an in vitro injection testing model. The normal distribution of the data was analyzed using the Kolmogorov-Smirnov test, while the homogeneity was assessed using Levene's test. Homogenous and normally distributed data were analyzed using a one-way analysis of variance (ANOVA) with a p-value of <0.05. The explored concentrations of PEGDMA-NFC included a ratio of 1:0 for the control samples and ratios of 1:0.5 (K1), 1:0.75 (K2), and 1:1 (K3) for the experimental samples. The FTIR analysis revealed the presence of various functional groups in PEGDMA-NFC, indicating its potential classification as a hydrogel biomaterial. The characterization data showed that the K3 sample yielded the most favourable outcome with a viscosity value of 74.67 dPa·s. From the in vitro injection testing result, the addition of NFC demonstrated that the hydrogel would not rupture when released from the mold. The hydrogel could be injected with an 18 gauge needle. The statistical analysis results showed a significant difference among the samples (p<0.05). This study concludes that the PEGDMA-NFC hydrogel biocomposite can be effectively applied in herniated nucleus pulposus cases.